An algebra problem by sumantra chatterjee

Algebra Level pending

If the roots of the equation ax^4+ax^3+bx^2+cx+d=0 are in GP then

c^2=(a^2)×(b^2) a^2=b b^2=ac c^2=(a^2)×d

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Let p, q, r, s be the roots of the equation. Then pqrs=d and since p, q, r, s are in GP hence d=(ps)^2 as ps=qr. Now [(p+q+r+s)/ps]=(-a/ps) or (1/p+1/q+1/r+1/s)=(-a/ps). Again 1/p,1/q,1/r,1/s are the roots of equation dx^4+cx^3+bx^2+ax+1=0. Therefore 1/p+1/q+1/r+1/s=(-c/d). So (-a/ps)=(-c/d). So [a^2/(ps)^2]=c^2/d^2. So a^2/d=c^2/d^2. So finally a^2×d=c^2.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...